Controlled growth of TiO2 nanoparticles on graphene by hydrothermal method for visible-light photocatalysis - Thanh-Lieu T.Le (Journal of Science: Advanced Materials and Devices, 2021)
This work presents the controlled synthesis of TiO2/graphene photocatalysts by hydrothermal method using TiCl4 as the precursor. The influence of the precursor concentration and the reaction time on the growth of TiO2 nanoparticles on graphene is studied and results in the ability to achieve the catalysts with desired TiO2 loadings and dispersion. By means of XPS, Raman, and UV-VIS diffuse reflectance spectroscopies, the chemical composition, the interaction between TiO2 and graphene, and the optical properties of the photocatalysts are investigated. The results reveal that the coupling with graphene considerably narrows the bandgap of TiO2, which stimulates the photocatalytic activity of TiO2/graphene under visible light irradiation. The photocatalytic performance of TiO2/graphene is studied by the degradation of RhB, which is carried out for the catalysts with TiO2 loadings in the range of 5–84%. The highest performance is achieved for the catalysts containing well-dispersed TiO2 nanoparticles on the graphene surface with loadings in the range between 16.5 and 26%. The degradation mechanism of RhB is further elucidated by using carrier and radical scavengers, which reveal the dominating role of holes and OH∗ radicals.